2006
DOI: 10.1111/j.1750-3841.2006.00087.x
|View full text |Cite
|
Sign up to set email alerts
|

A Continuous High‐Pressure Carbon Dioxide System for Cloud and Quality Retention in Orange Juice

Abstract: Orange juice (OJ) was treated with a continuous high‐pressure carbon dioxide (HPCD) system, and the quality parameters pH, Brix, titratable acidity (TA), cloud, pectinesterase (PE) activity, color, and sensory attributes were determined. Treatment pressures were 38, 72, and 107 MPa, and CO2/juice (w/w) ratios were from 0.40 to 1.18. Residence time was kept at 10 min. Cloud increased between 446% and 846% after treatments. There were no significant changes in pH and Brix (α= 0.05). TA of the treated juice was f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
95
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(115 citation statements)
references
References 12 publications
19
95
1
Order By: Relevance
“…Hence, there was no change in the pH was observed in muscadine grape juice, after the removal of CO 2 by vacuum during the last stage of dense phase CO 2 processing (Pozo-insfran et al 2007). However, pH did not change in orange juice after HPCD treatment (Kincal et al 2006). It was because that the dissociation constants of carbonic acid and bicarbonate were pKa=6.57 and pKa= 10.62 (Damar and Balaban 2006), the low pH in the original orange juice resulted in the carbonic acid formed by CO 2 dissolving into the juice difficultly being dissociated into H + ions.…”
Section: Resultsmentioning
confidence: 98%
“…Hence, there was no change in the pH was observed in muscadine grape juice, after the removal of CO 2 by vacuum during the last stage of dense phase CO 2 processing (Pozo-insfran et al 2007). However, pH did not change in orange juice after HPCD treatment (Kincal et al 2006). It was because that the dissociation constants of carbonic acid and bicarbonate were pKa=6.57 and pKa= 10.62 (Damar and Balaban 2006), the low pH in the original orange juice resulted in the carbonic acid formed by CO 2 dissolving into the juice difficultly being dissociated into H + ions.…”
Section: Resultsmentioning
confidence: 98%
“…The change in colour, ∆E (Eq 3) is also presented in Table 6 and visible 385 differences in colour after HPCD treatment have been determined (∆E ≈ 5). Kincal et al (2006) 386 also reported ∆E values as high as 13.83, at 72 MPa and a ratio of 0.64 CO 2 /juice (w/w). Chroma 387 values listed in Table 6 show that HPCD treatment results in a significant lower colour intensity 388 juice after processing but no significance differences have been observed along storage.…”
Section: =2·10mentioning
confidence: 94%
“…The faster 207 inactivation reached in our work could be due to the way CO 2 was fed into the sample through 208 CO 2 -microbubbles, which helps to maximizes the interface area for the orange juice and the 209 CO 2 . Inactivation percentages slightly higher than 50 % were reached when using a continuous 210 HPCD system (Kincal et al, 2006). Table 1 also presents the inactivation degree of PME in 211 orange juice when using a combined technology of high power ultrasound-assisted supercritical 212 carbon dioxide (HPU-SCCO 2 ).…”
Section: Reached a 100% Of Inactivation In A Milton 203mentioning
confidence: 99%
See 2 more Smart Citations